The Impact of Diet and Lifestyle on the Course of Autoimmune Diseases - Sobek, Karolina Łucja; Mazur, Michał; Waz, Dorota; Szarłowicz, Jakub; Goliszek, Zofia; Tabin-Barczak, Wiktoria; Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil; Samuła, Sebastian (Quality in Sport, 2024)
Introduction and Purpose: Autoimmune diseases represent a diverse group of disorders caused by immune dysregulation, resulting in attacks on the body’s own tissues. These conditions are increasingly common and significantly impact patients' quality of life. Environmental factors, including diet and lifestyle, are key contributors to this increase. This review explores the impact of diet and lifestyle on the progression and management of autoimmune diseases. Materials and Methods: This review is based on articles obtained from scientific databases like PubMed, selected for their importance to the subject. Results: Anti-inflammatory diets, such as the Mediterranean diet, omega-3 fatty acids, vitamin D, and selenium, reduce disease activity and modulate immune responses. Dysbiosis in the gut and oral microbiomes is a significant factor in disease progression, while probiotics and prebiotics may have a promising impact.Lifestyle factors complement dietary strategies by reducing systemic inflammation and improving physical and mental health. Gender-specific differences further highlight the need for personalized management approaches. Conclusion: Diet and lifestyle modifications significantly influence autoimmune disease outcomes by reducing inflammation, supporting immune regulation, and addressing comorbidities. Future research should focus on precision nutrition and microbiome-based therapies to further enhance treatment outcomes and patient well-being.